Informatics - ., . (Journal of Engineering Education Transformations, 2007)
The need for a consortium of Engineering Colleges and Polytechnics at various places in the state, either University wise / district wise or any area wise. Discussion ended with the formation of an an adhoc body for consortium at Pune city.